Laparoscopic versus robotic‐assisted radical prostatectomy: an Australian single‐surgeon series. Issue 3 (15th April 2014) - Papachristos, Alexander; Basto, Marnique; te Marvelde, Luc; Moon, Daniel
Abstract Background In Australia, robotic‐assisted radical prostatectomy (RARP) has steadily replaced open and laparoscopic surgery in the management of localized prostate cancer. Given the increased cost of this technology, we aimed to compare the perioperative, pathological, oncological and functional outcomes as well as short‐term complications of laparoscopic and RARP. Methods We performed a retrospective review of prospectively collected data on 200 consecutive patients during the transition of a single surgeon (DM) from pure laparoscopic (n = 100) to RARP (n = 100) between September 2007 and March 2011. Results Median operative time and estimated blood loss were the same for both surgical approaches, 195 min (P = 0.29) and 300 mL (P = 0.88) respectively. Median length of hospital stay was shorter for RARP (P = 0.003). Complication rates were not statistically different between groups. There was no significant difference in positive surgical margin rates in pT2 (P = 0.36) or pT3 disease (0.99) or biochemical recurrence rate between groups (P = 0.14). The 12 months continence rate was improved with RARP compared with laparoscopic radical prostatectomy (93% versus 82%; P = 0.025). The potency rate was 56% and 74% at 12 months after laparoscopic radical prostatectomy and RARP respectively (P = 0.12) for a bilateral nerve sparing procedure. Conclusion We conclude from our single‐surgeon comparative series that the robotic approach results in a significantly shorter length of hospital stay and improved 12 months continence rates and demonstrated a trend towards better potency rates. Complications, positive surgical margin rates and the requirement for adjuvant therapy are all improved with the robotic approach but did not show statistically significant differences.